Propionate Ameliorates Dextran Sodium Sulfate-Induced Colitis by Improving Intestinal Barrier Function and Reducing Inflammation and Oxidative Stress - Tong, Ling-chang; Wang, Yue; Wang, Zhi-bin; Liu, Wei-ye; Sun, Sheng; Li, Ling; Su, Ding-feng; Zhang, Li-chao (Frontiers in Pharmacology, 2016)
Propionate is a short chain fatty acid and abundant as butyrate in the gut and blood. However, propionate has been studied less extensively than butyrate in the treatment of colitis. The present study was to investigate the effects of sodium propionate on intestinal barrier function, inflammation and oxidative stress in dextran sulfate sodium (DSS)-induced mice. Animals in DSS group received drinking water from 1 to 6 days and DSS (3% (w/v) dissolved in double distilled water) instead of drinking water from 7 to 14 days. Animals in DSS+Prop group were given 1% sodium propionate for 14 consecutive days and supplemented with 3% DSS solution on day 7-14. Intestinal barrier function, proinflammatory factors, oxidative stress, and signal transducer and activator of transcription 3 (STAT3) signaling pathway in the colon were determined. It was found that sodium propionate ameliorated body weight loss, colon-length shortening and colonic damage in colitis mice. Sodium propionate significantly inhibited the increase of FITC-dextran in serum and the decrease of zonula occludens-1 (ZO-1), occludin and E-cadherin expression in the colonic tissue. It also inhibited the expression of interleukin (IL)-1β, IL-6 and tumor necrosis factor-α (TNF-α) mRNA and phosphorylation of STAT3 in colitis mice markedly, reduced the myeloperoxidase (MPO) level, and increased the superoxide dismutase (SOD) and catalase (CAT) level in colon and serum compared with DSS group. Sodium propionate inhibited macrophages with CD68 marker infiltration into the colonic mucosa of colitis mice. These results suggest that oral administration of sodium propionate could ameliorate DSS-induced colitis mainly by improving intestinal barrier function and reducing inflammation and oxidative stress via the STAT3 signaling pathway.